Freezing the polarization of CH3NH3PbI3 and CH3NH3PbI3-xClx perovskite films. (June 2017) - Stumpp, Martina; Ruess, Raffael; Müßener, Jan; Schlettwein, Derck
Abstract: Thin films of methylammonium lead halides, CH3 NH3 PbI3 and CH3 NH3 PbI3-x Clx, were deposited onto symmetrical microstructured electrode arrays of gold or platinum on Si/SiO2 wafers. Polarization studies were carried out on perovskite films under vacuum in the dark. For poling, a constant voltage was applied to the samples while the temperature was cycled between 295 K and 4 K. The measured current densities depending on the temperature showed distinct characteristics relating strongly to the crystal phase and the dielectric properties of the perovskite films. Voltage sweeps were carried out at different scan rates at specific temperature intervals after poling. The polarization of the films due to the migration of iodide vacancies in direction of the blocking perovskite/metal interface was frozen almost up to room temperature. Charge carriers were only able to cross the blocking barrier and contribute to the current where the ions have accumulated during poling. All J-V curves showed hysteresis: inverted and regular hysteresis at room temperature and below, respectively. Inverted hysteresis originates from the slow accumulation of ions at the blocking barrier, while regular hysteresis arises from a distortion in the adjacent crystals which will be discussed. Graphical abstract: Highlights: The crystal phase and dielectric properties of perovskite films strongly influence the current across contacts to metals. The conduction is limited by crossing the Schottky barrier at the metal/perovskite interface. J-V hysteresis at this barrier is caused by ion movement and lattice distortions, both depending on temperature. Ions accumulated at the perovskite/metal interface by an applied electric field can be fixed here by cooling to 4 K.